Seleksi Penerimaan Staff Admin Gudang Menggunakan Metode Preference Selection Index (PSI) - Yunita Rahma; Sufiatul Maryana (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
Selection of warehouse admin staff is a crucial process in ensuring operational sustainability and warehouse management efficiency. The application of the Decision Support System (DSS) in the selection process for warehouse admin staff recruitment can provide significant benefits in increasing the efficiency and accuracy of the process. With the application of the PSI method in the recruitment of warehouse admin staff, it can help companies provide recommendations for selection results by applying a decision support system model. The ranking results using the PSI method recommend the first place with a final value of 0.882 obtained by Haris, the second place with a final value of 0.842 obtained by Budiman, and the third place with a final value of 0.800 obtained by Handoyo.